INVESTIGATION OF CRITICAL MATERIAL ATTRIBUTES OF NANOCELLULOSE IN TABLETS - ROSHNI VORA; YAMINI SHAH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present work aims to compare powder flow properties and post-compression characteristics of acid hydrolysis nanocellulose (AH-NC) a novel excipient with microcrystalline cellulose (MCC PH200) to demonstrate the application and performance of AH-NC. Methods: I-optimal design was applied separately for both the excipient, i.e., MCC PH200 and AH-NC. Independent variables were MCC PH200 as diluent (X1), AH-NC as diluent (X1), starch as disintegrant (X2), and PVP K30 as dry binder (X3). The dependent variables in design were Carr’s index (CI) (R1), angle of repose (AR) (R2), hardness (R3), friability (R4), disintegration time (DT) (R5), and T90 (R6). Results: Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry studies showed the compatibility of the drug with an excipient. CI was found in the range of 8%–17.84% for MCC PH200 and 5.25%–11.94% for AH-NC. AR was found in the range of 31.48–37.66 for MCC PH200 and 29.62–35.30 for AH-NC. The values of friability, DT, and T90 were almost identical in both the cases. Conclusion: Not only does AH-NC demonstrates better flow properties but also problems of weight variation and content uniformity are not observed when compared to MCC PH200. Hence, AH-NC is more suitable as an excipient for modern high-speed rotary tablet press.